A horizontal–vertical anisotropy in spatial short-term memory. Issue 4 (21st April 2022) - Smith, Daniel T.
ABSTRACT: Visual perception and saccadic eye-movements are more precise when directed at isoeccentric locations along the horizontal compared to vertical meridian. This effect is known as horizontal-vertical anisotropy (HVA). Given that the eye-movement system plays an important role in spatial short-term memory (STM) it was hypothesized that spatial STM would also show a horizontal-vertical anisotropy. Consistent with this hypothesis an online experiment revealed a significant HVA in spatial STM (Experiment 1). This effect persisted even when eye-movements were precluded by using very short display durations (Experiment 2). However, there was no HVA in a colour span or orientation change detection task. It is argued that the HVA in spatial STM may result from greater imprecision in the representation of spatial locations along the vertical meridian relative to the horizontal meridian in the spatial maps underpinning spatial STM, a bilateral field advantage, or some combination of these mechanisms.